Sejarah Kelas Menulis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung - Susanti Vera; Fitriani Fitriani; Hidayatul Fikra (Gunung Djati Conference Series, 2024)
This research aims to tell the history of the Writing Class at the Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung. This research uses a qualitative approach with genealogical methods. The results and discussion of this research show that the Writing Class was formally established on May 29 2020. Meanwhile, the term Writing Class imitates the use of the term Writing Center in various advanced higher education in the global world. The Writing Class acts as a support center for increasing students' skills capacity in academic writing for the purposes of scientific publications. This research concludes that the establishment of the Writing Class genealogically began with the implementation of the Writing School which has been taking place culturally at UIN Sunan Gunung Djati Bandung since 2016.